SOME FEATURES OF MAINTAINING ATTORNEY-CLIENT PRIVILEGE IN MODERN RUSSIAN LEGAL REALITY - Петрова, Роза Есеновна; Пиксин, Дмитрий Григорьевич (Правовое государство: теория и практика, 2022)
The institution of attorney-client privilege, designed to advance the constitutional provision relating to the preservation of privacy, is undergoing major changes in connection with the development of information technologies. Lawyers and members of lawyers' associations are actively using computerized systems, databases to facilitate the provision of qualified legal assistance. It is information containing data relating to attorney-client privilege that is of interest to persons capable of gaining access to other people's computers. Purpose: to analyze the institution of attorney-client privilege, as well as the status of persons who have access to it. In addition, it is necessary to classify the sources of attorney-client privilege, as well as to study the mechanism of their action. Methods: in the course of writing the work, the dialectical method, analysis, synthesis, comparative legal, description method and legal modeling method are used. Results: the authors investigate the problem of the institution of attorney-client privilege, the mechanisms of its preservation and provision. Some contradictions are revealed between the legislative definition of the institution of attorney-client privilege and the definition popular in the lawyers' community. In addition, the role of members of lawyers' associations with access to attorney-client privilege is studied. A classification of sources of attorney-client privilege is made, and methods of modernization of the said institute are proposed, which is expressed in approval or criticism of the positions of some authors regarding the problem of preservation of information containing attorney-client privilege.